Ultrasonographic prediction of birth weight discordance in twin pregnancies. (6th July 2015) - van de Waarsenburg, M. K.; Hack, K. E. A.; Rijpma, R. J.; Mulder, E. J. H.; Pistorius, L.; Derks, J. B.
Abstract Objective This study aimed to assess the accuracy of the ultrasonographic prediction of intertwin birth weight discordance based on crown–rump length, estimated fetal weight (EFW) and abdominal circumference. Method We retrospectively studied variables of prenatal surveillance of 281 twin pregnancies at the University Medical Centre Utrecht, between 2008 and 2011. Results Fifteen per cent of twins had a birth weight discordance of ≥20%. One twin more commonly had intrauterine growth restriction in the birth weight discordance group compared with the concordantly grown group (69% vs 20%, respectively). Sonographically, EFW discrepancy and increased abdominal circumference ratio were significantly correlated with birth weight discordance. The negative predictive values were high (92% and 87%, respectively). The best prediction of weight discordance was given by EFW discordance at the last ultrasound before delivery. Conclusion Intertwin birth weight discordance is best predicted by an intertwin EFW discordance at the last ultrasound. If discordance is not suspected by ultrasound, the vast majority had no birth weight discordance. In case of birth weight discordance, the presence of at least one growth‐restricted twin is very likely. However, because around 20% of concordantly grown twin pairs comprise at least one intrauterine growth restriction infant, one cannot rely on weight discordance alone. © 2015 John Wiley & Sons, Ltd.